Integrated narrative nursing: a new perspective for an advanced assessment - Artioli, Giovanna; Foà, Chiara; Cosentino, Chiara; Taffurelli, Chiara (Acta Biomedica Atenei Parmensis, 2017)
The assessment is the first of the fundamental nursing processes: it includes data collection, problem identification, and setting of priorities, which all facilitates the process of making a nursing diagnosis. The assessment helps to identify a goal, which, through a decision-making process, orientates the planning as well as the nursing intervention, which will be evaluated at a later stage. It seems that the proposed multidimensional and integrated assessment has a good potential to significantly influence the nursing care. This model is multidimensional since it covers biophysical, psychological, socio-relational, but also the spiritual dimensions of each person, and is integrated since it’s reinforced by the inter-professional dialogue between nurses, physicians, sociologists, psychologists, and other health professionals. To come up with a diagnosis, nurses integrate the “cases” (the set of data/information collected through a “traditional” assessment), with the “stories” (which are directly narrated from the people themselves). Thus the proposed model combines quantitative instruments, typical of natural sciences (questionnaires, scales, tests and surveys), with qualitative ones, deriving from human sciences (interviews, the patient’s agenda and narratives). The complementary use of objective and subjective methods leads to valid, consistent and standardized results, and, at the same time, makes it possible to investigate unique and subjective perceptions. Several strategies are outlined in this paper, with methods, phases and instruments related to the advanced assessment model, in order to better determine the most suitable based on the person’s individual needs.